Vertigo and Severe Balance Instability as Symptoms of Lyme Disease—Literature Review and Case Report - Jozefowicz-Korczynska, Magdalena; Zamyslowska-Szmytke, Ewa; Piekarska, Anna; Rosiak, Oskar (Frontiers in Neurology, 2019)
Lyme disease is caused by a tick-borne bacterium Borrelia sp. This zoonotic infection is common in the Northern Hemisphere e.g. Europe. Clinical presentation may involve multisystem symptoms and depends on the stage of the disease. The involvement of nervous system in Lyme disease is commonly referred to as neuroborreliosis. Neuroborreliosis may involve meningitis, mononeuritis multiplex or cranial neuritis including the inflammation of vestibulocochlear nerve. In the late or chronic stage of Lyme disease, vestibular involvement may be the sole presentation, although such cases are rare. Our study was designed to present our own case and review the available literature reporting cases of neuroborreliosis with vertigo/dizziness and severe balance instability as a main disease symptom. The studies were obtained by searching the following databases: PUBMED, Medlince, and Embase. We included case reports of Lyme disease presenting with vertigo or gait disorders as main symptom, written in the English language. Initially, 60 papers were identified. After analyzing the abstracts, seven manuscripts focusing on 13 clinical cases were included in this review. We conclude that the patients with neuroborreliosis sometimes present vertigo/dizziness, but rarelygait ataxia as a sole symptom. These complaints are usually accompanied by a hearing loss. Antibiotic treatment is usually effective. Balance instability in the patients with neuroborreliosis may persist but it responds well to vestibular rehabilitation.